Factors Associated with Success in Revision Surgery for Infected Hip and Knee Arthroplasties. (4th October 2017) - Kandel, Christopher; Backstein, David; Sajja, Abhilash; McGeer, Allison
Abstract: Background: Patients with prosthetic joint infections (PJIs) often fail treatment. We aimed to describe the characteristics and outcomes of PJIs managed at a tertiary institution in Canada. Methods: We assembled a cohort of patients undergoing surgical revision for hip or knee PJIs from January 1, 2010 until December 31, 2014 at our referral hospital by searching procedure descriptions from operative listings. Patient characteristics were abstracted by chart review. Treatment failure (TF) was defined by PJI recurrence requiring surgery, receipt of suppressive antimicrobials, amputation, excision or death. Results: 243 individuals with a PJI undergoing a revision surgery were included. Median age was 69 years, 111 (46%) were males, 118 (49%) involved hips, 125 (51%) were knees, incision and drainage was performed in 53 (22%), a two-stage procedure was undertaken in 168 (69%), and a one-stage procedure in 18 (7%). Most PJIs were monomicrobial (50%); with coagulase negative staphylococci (35%) and Staphylococcus aureus (18%) the most common. TF occurred in 85/171 (47%): 53 (62%) required revision surgery, 23 (27%) chronic suppressive antimicrobials, 5 (6%) amputation, and 4 (5%) died (Table 1). On univariate analysis incision and drainage was associated with failure (OR 2.8, 95% CI 1.3–5.8, P = 0.002) while a two-stage procedure (OR 0.4, 95% CI 0.2–0.8, P = 0.009) and chronic symptoms (OR 0.4, 95% CI 0.2–0.8, P = 0.008) were protective. No risk factors for TF were identified on multivariable analysis. Conclusion: PJIs are challenging to eradicate. New treatment paradigms are needed. Disclosures: A. McGeer, Hoffman La Roche: Investigator, Research grant. GSK: Investigator, Research grant. Sanofi pasteur: Investigator, Research grant